2008
DOI: 10.1002/hed.20907
|View full text |Cite
|
Sign up to set email alerts
|

Nodal metastases at level IIb during neck dissection for head and neck cancer: Clinical and pathologic evaluation

Abstract: The incidence of metastases at level IIb is low, also in the N+ necks, therefore dissection of this level could be unnecessary in N0 necks. Furthermore, an interesting statistical association between the presence of metastases at level IIb and at level IIa was recorded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 21 publications
1
32
0
Order By: Relevance
“…Radical neck dissection or modified radical neck dissection is the surgical treatment of choice in patients with carcinoma of the hypopharynx with clinical N+ neck [30]. On the other hand, the incidence of occult nodal metastasis in patients with hypopharyngeal cancer is found to be more than 20% [31]. The lack of investigation modality with satisfactory sensitivity and specificity to detect such microscopic metastasis, together with the apparently poor locoregional disease control as well as distant metastasis with wait-and-see strategy makes prophylactic neck dissection a logical option for patients with clinically N0 neck [32].…”
Section: Management Of the Neckmentioning
confidence: 98%
“…Radical neck dissection or modified radical neck dissection is the surgical treatment of choice in patients with carcinoma of the hypopharynx with clinical N+ neck [30]. On the other hand, the incidence of occult nodal metastasis in patients with hypopharyngeal cancer is found to be more than 20% [31]. The lack of investigation modality with satisfactory sensitivity and specificity to detect such microscopic metastasis, together with the apparently poor locoregional disease control as well as distant metastasis with wait-and-see strategy makes prophylactic neck dissection a logical option for patients with clinically N0 neck [32].…”
Section: Management Of the Neckmentioning
confidence: 98%
“…11,12 Furthermore, to minimise post-operative morbidity, super-selective dissection of sublevels IIa-III has recently been proposed because of the rare involvement of sublevel IIb and level IV in clinically staged N 0 laryngeal carcinomas. 16,17 In a previously irradiated neck, however, the usual regional lymphatic pathway for both the larynx and neck may have been extensively modified by radiation-induced sclerosis of the lymphatic vessels. Hence, a post-RT recurrent laryngeal tumour could spread to lymph nodes beyond the original predicted pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Level IIa were found to be positive for lymph nodes metastasis for all patients of positive level IIb. 8 In Talmi et al, 15 four out of 102 neck dissections had level IIb lymph nodes metastasis. All of the four neck dissections had level IIa lymph node metastasis and were advanced pathological N staging.…”
Section: Discussionmentioning
confidence: 98%
“…That is why obtaining frozen section biopsy intraoperatively is highly recommended to identify these factors. 4 Other study 8 found it to be inaccurate to perform frozen section biopsy to identify level IIa lymph nodes occult metastasis. One study 14 suggests removing this level in clinically N+ necks, but mostly avoided in clinical N0.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation